2015
DOI: 10.1097/htr.0000000000000050
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Care Pathways and Outcome 1 Year After Severe Traumatic Brain Injury

Abstract: Delays in rehabilitation admission were negatively associated with outcome. Measures to ensure timely rehabilitation admission may improve outcome. Further research is needed to evaluate possible causation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…In a previous study, 2 we found that, having controlled for acute prognostic variables known to impact on outcome, length of stay in intensive care, time between intensive care and rehabilitation admission, and the presence of any medical complication 3 weeks after injury were all associated with unfavourable outcome 1 year after injury. In this study, we explore further rates of specific complications and associations of these with outcome at 1 year.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In a previous study, 2 we found that, having controlled for acute prognostic variables known to impact on outcome, length of stay in intensive care, time between intensive care and rehabilitation admission, and the presence of any medical complication 3 weeks after injury were all associated with unfavourable outcome 1 year after injury. In this study, we explore further rates of specific complications and associations of these with outcome at 1 year.…”
Section: Introductionmentioning
confidence: 80%
“…This study formed part of a prospective, multicentre, observational study of patients who had sustained severe TBI (the ‘PROBRAIN’ study 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Several variables that capture the patient's status upon admission to rehabilitation appear to be a proxy for the severity of the index injury and hold considerable predictive power for rehabilitation outcomes (e.g., time from injury to rehabilitation admission, functional independence at admission, presence of agitation or other pathognomonic signs). 2,10,11 …”
mentioning
confidence: 99%
“…[16][17][18] Study design has been described previously. 16,17 In brief, inclusion criteria were severe, non-penetrating, traumatic brain injury requiring neurointensive care, with acute Glasgow Coma Scale score of [3][4][5][6][7][8]19 in adult patients aged 18-65 years. Exclusion criteria were death or expected death within 3 weeks of injury.…”
Section: Methodsmentioning
confidence: 99%